Seaweed Loads Cause Stronger Bacterial Community Shifts in Coastal Lagoon Sediments Than Nutrient Loads - Aires, Tânia; Muyzer, Gerard; Serrão, Ester A.; Engelen, Aschwin H. (Frontiers in Microbiology, 2019)
Nutrients input from anthropogenic sources are the leading causes of coastal eutrophication and are usually coupled with algal/seaweed blooms. Effects may be magnified in semi-enclosed systems, such as highly productive coastal lagoon ecosystems. Eutrophication and seaweed blooms can lead to ecosystem disruption. Previous studies have considered only one of these factors, disregarding possible interactive effects and the effect of the blooming species' identity on sediment bacterial communities. We tested the effect of experimental nutrient loading and two common blooming seaweeds (Ulva rigida and Gracilaria vermiculophylla) in coastal lagoon sediments, on the structure of bacterial communities (using 16S rRNA amplicon sequencing) and corresponding putative functional potential (using PiCRUSt). At the Operational Taxonomic Unit (OTU) level, the addition of nutrients reduced bacterial community α-diversity and decreased abundance of sulphate reducers (Desulfobacterales) compared to sulphur oxidizers/denitrifiers (Chromatiales and Campylobacterales), whereas this was not the case at the order level. Seaweed addition did not change bacterial α-diversity and the effect on community structure depended on the taxonomic level considered. Addition of Gracilaria increased the abundance of orders and OTUs involved in sulphate reduction and organic matter decomposition (Desulfobacterales, Bacteroidales and Clostridiales, respectively), an effect which was also detected when only Ulva was added. Nutrients and seaweeds combined only interacted for Ulva and nutrients, which increased known sulphide oxidizers and denitrifiers (order Campylobacterales). Seaweed enrichment affected putative functional profiles; a stronger increase of sulphur cycling KEGG pathways was assigned to nutrient-disturbed sediments, particularly with seaweeds and especially Ulva. In contrast, nitrogen and sulphur cycle pathways showed higher abundance of genes related to DNRA in Ulva+nutrients treatments. However, the other seaweed treatments increased nitrogen fixation genes. Thiosulfate reduction, performed by sulphate-reducing bacteria, increased in seaweed treatments except when Ulva was combined with nutrients. Concluding, in situ addition of nutrients and seaweeds to intertidal sediments affected the bacterial communities differently and independently. The predicted functional profile suggests a shift in relative abundances of putative pathways for nitrogen and sulphur cycles, in line with the taxonomic changes of the bacterial communities.